Isolated prolongation of activated partial thromboplastin time in intensive care unit patients: a practical diagnostic algorithm and management options - Czempik, Piotr F.; Żurawska, Elżbieta; Krzych, Łukasz (Anestezjologia Intensywna Terapia, 2020)
Abnormal values for standard laboratory tests of coagulation are frequently reported in critically ill patients. Sepsis-associated coagulopathy with prolonged prothrombin time and thrombocytopenia is common among patients hospitalized in the intensive care unit (ICU). Isolated prolongation of activated partial thromboplastin time (aPTT) occurs less frequently in the ICU setting and has numerous causes. Moreover, there are several preanalytical factors that may impact on results obtained. Isolated prolongation of aPTT in the absence of clinically relevant bleeding is a common finding in patients in the ICU. The first step in the diagnostic process is exclusion of preanalytical error. Next, based on the clinical picture (normal haemostasis vs. bleeding tendency), the appropriate tests should be ordered, taking into account acquired and congenital causes. To establish a diagnosis in a timely fashion, the proposed practical diagnostic algorithm can be followed.